2011
DOI: 10.1177/147470491100900314
|View full text |Cite
|
Sign up to set email alerts
|

The Affective Quality of Human-Natural Environment Relationships

Abstract: Using a psychometric methodology the present study explored the associations between natural environments and experiential feeling states. The effects of the frequency of participants" (N = 90) experience of the natural environment and of the location of their childhood upbringing were also investigated. Ten natural environments mapped on to an orthogonal two-component experiential structure labeled Eudemonia (ostensibly positive feelings) and Apprehension (ostensibly negative feelings). Generally, the more na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 60 publications
3
56
1
1
Order By: Relevance
“…Hinds (2011), for this is where the individual can be free of the distractions of modern living and the senses can attend to the natural world. Hinds and Sparks (2011) found that wild landscapes were associated with greater "Eudemonia" than more managed landscapes, such as farmland. However, there is little wilderness in the UK and with progressive urbanisation nature is most accessible in a rural or semi-rural landscape.…”
Section: Mindfulness In Naturementioning
confidence: 98%
“…Hinds (2011), for this is where the individual can be free of the distractions of modern living and the senses can attend to the natural world. Hinds and Sparks (2011) found that wild landscapes were associated with greater "Eudemonia" than more managed landscapes, such as farmland. However, there is little wilderness in the UK and with progressive urbanisation nature is most accessible in a rural or semi-rural landscape.…”
Section: Mindfulness In Naturementioning
confidence: 98%
“…States such as amazement, awe and wonder have been associated with eudemonic aspects of experience and therefore are differentiable from happiness [25]. Nature is known to be associated with positive feelings, such as awe and wonder [26,27] and wonder is often noted in observations of everyday nature [28]. Again, such emotional responses are associated with enhancing nature connectedness [29,30].…”
mentioning
confidence: 99%
“…A biophilic city can ensure a healthier and more comfortable life in many other ways as well. One study found that living far from green areas can be a factor behind the deterioration of physical health (Hinds-Sparks 2011). One of the main negative consequences of uncontrollable urbanisation is air pollution.…”
Section: Biophilic Cities As a Key To Sustainabilitymentioning
confidence: 99%